MODALITY IN GIVING ADVICE IN AN INDONESIAN EFL TEXTBOOK: INSIGHTS FROM SYSTEMIC FUNCTIONAL LINGUISTICS - Siburian, Irene Nataly; Yogi Setia Samsi; Kelik Wachyudi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Modality plays an important role in expressing interpersonal meaning, particularly in giving advice within English language teaching materials. This study investigates the realization of modality in giving advice in the Indonesian EFL textbook Interactive English 2 and explores its pedagogical implications. The study employed a qualitative document analysis. The research corpus consisted of clauses realizing giving advice, identified from Unit 1 of the textbook after all instructional units had been systematically screened. The findings revealed that giving advice was predominantly realized through the modal operators should and shouldn't. The analysis showed that "should" occurred more frequently than "shouldn't," indicating the textbook's preference for positive recommendations over prohibitive advice. These expressions were integrated into listening dialogues, grammar explanations, reading passages, communication activities, speaking tasks, and evaluation exercises, allowing learners to encounter advice in meaningful communicative contexts. The findings suggest that the textbook presents modality not only as a grammatical feature but also as an interpersonal resource that supports communicative and pragmatic competence. The study concludes that integrating modality into contextualized instructional activities facilitates meaningful English language learning and provides practical implications for English teachers and textbook developers.